2018
DOI: 10.1016/j.wjorl.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The infrahyoid myocutaneous flap for reconstruction after oral cancer resection: A retrospective single‐surgeon study

Abstract: ObjectiveTo review our experience with infrahyoid myocutaneous flap in reconstruction after oral cancer resection.MethodsChart reviews were completed for all patients who underwent oral reconstruction with an infrahyoid myocutaneous flap by a single surgeon in the Department of Otolaryngology at Chonburi Cancer Hospital from 2011 to 2017. Characteristics of the patients and postoperative complications were analyzed.ResultsOf the 34 patients in the study, 10 (29.4%) developed partial flap loss and 1 (2.9%) deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…The study concluded that IHF was a fairly reliable reconstruction method and the flap should be performed with caution in cases with gross lymph node involvement. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that IHF was a fairly reliable reconstruction method and the flap should be performed with caution in cases with gross lymph node involvement. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…Complications related to this flap mentioned in literature are unreliability of skin paddle and partial skin necrosis. [ 6 ] However, despite so many advantages, this flap is underused for head and neck reconstructions.…”
Section: Introductionmentioning
confidence: 99%
“…From the 13 oncological cases, 4 did not underwent adjuvant treatment, one underwent radiation alone, 6 radiation and chemotherapy and the thyroid carcinoma case underwent radioiodine ablation and external beam radiation is scheduled (Table 1). harvest flap suitable for medium sized defects of the head and neck region 6,17,28 . The preservation of the ansa cervicalis allows functional recovery for mobile tongue reconstruction by preventing muscle atrophy and by continuous stimuli during deglutition 7,17 .…”
Section: Discussionmentioning
confidence: 99%
“…① Comparison of clinical symptom scores: symptoms included insomnia, nausea and vomiting, pain, fatigue, and diarrhea and were rated (on a 0-100 scale) by reference to the visual analogue scale (VSA) for pain, with lower scores indicating less symptoms ② Comparison of CR: complications included incision infection, necrosis of skin flap, wound bleeding, and stress ulcer ③ Comparison of UW-QOL scores: the score was rated based on the University of Washington Quality of Life Questionnaire (UW-QOL) of head and neck cancer patients on a scale of 0-100, with lower scores indicating worse quality of life [8][9][10][11] ④ Investigation on factors affecting patients' quality of life, which was carried out by self-designed questionnaire ⑤ Comparison of negative emotion scores of patients after intervention. The scores (on a scale of 0-100) of patients' self-rating anxiety scale (SAS) and self-rating depression scale (SDS) were compared, with higher scores indicating heavier negative emotion [12][13][14][15] 2.6. Statistical Processing.…”
Section: Nursing Interventionmentioning
confidence: 99%